1982
DOI: 10.1128/aac.21.2.339
|View full text |Cite
|
Sign up to set email alerts
|

Lack of in vitro activity of cefoxitin, cefamandole, cefuroxime, and piperacillin against Chlamydia trachomatis

Abstract: Newer penicillins and cephalosporins are being evaluated in many infections. One of these infections, acute pelvic inflammatory disease, can be caused by Chlamydia trachomatis. This study demonstrated that cefoxitin, cefamandole, cefuroxime, and piperacillin had no effective in vitro activity against C. trachomatis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
1

Year Published

1983
1983
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
1
1
1
Order By: Relevance
“…In contrast, with penicillins there are occasional inclusions over a wide range of concentrations (6,10,14,15). This probably accounts for the large discrepancies in published reports of MICs of penicillins (4,6,9,10,(13)(14)(15)(16). In vivo, single-dose penicillin treatment does not usually eradicate C. trachomatis (7, 10), but multiple-dose penicillin treatment often results in negative follow-up cultures for weeks or longer (2,5,7,12).…”
contrasting
confidence: 44%
“…In contrast, with penicillins there are occasional inclusions over a wide range of concentrations (6,10,14,15). This probably accounts for the large discrepancies in published reports of MICs of penicillins (4,6,9,10,(13)(14)(15)(16). In vivo, single-dose penicillin treatment does not usually eradicate C. trachomatis (7, 10), but multiple-dose penicillin treatment often results in negative follow-up cultures for weeks or longer (2,5,7,12).…”
contrasting
confidence: 44%
“…The most active drug was mecillinam, which had a mean MIC of 0.45 ,ug/ml and an MCC of 0.5 jxg/ml. Overall, our results agree closely with those of previous studies (1,3,5,6,7), with the exception of piperacillin. Bowie (1) reported piperacillin MICs of .4,096 ,ug/ml by methods, including iodine staining, very similar to ours.…”
supporting
confidence: 83%
“…Penicillins have been reported to eradicate C. trachomatis in eight of ten women treated with a 21-day course of ampicillin for cervical and/or urethral infection. 8 Bowie et al reported the microbiological cure in six of six men with urethritis when treated with a 10-day regimen of amoxicillin. 9 Martin et al reported the microbiological cure of C. trachomatis infection in seven patients treated with ticarcillin/clavulanic acid, whereas three patients treated with cephalosporins remained culture positive after treatment.…”
mentioning
confidence: 99%